Energy harvesting from inline vibration of an elastically mounted circular cylinder in oscillatory flow. (1st November 2021) - Taheri, Erfan; Zhao, Ming; Wu, Helen; Munir, Adnan
Abstract: Harvesting energy from ocean waves has attracted increasing attention due to the depletion of fossil fuels. Water motion under ocean waves can be modelled as oscillatory flow when its impact on small-scale structures are studied. In this paper, energy harvesting from inline vibration of an elastically mounted circular cylinder in oscillatory flow is studied numerically at a low Reynolds number of 150, two Keulegan–Carpenter ( KC ) numbers of 5 and 10 and three mass ratios of 1, 2 and 3. The energy-harvesting device is an electromagnetic device comprising of electric coils and a magnet. For specific KC number, mass ratio and electromagnetic damping ratio, the maximum power occurs when the natural frequency of the cylinder measured in water is the same as the oscillatory flow frequency and is defined as lock-in power. For a fixed flow condition, the lock-in power is affected by the electromagnetic damping ratio and there exists a best electromagnetic damping ratio, where the lock-in power reaches its maximum value, which is defined as the best power. The best power is found to be independent of the mass ratio and decreases with the increase of KC number. The best electromagnetic damping ratio decreases with the increase of mass ratio and increase with the increase of KC number. The irregular vibration of the cylinder at KC = 10 causes significant reduction in the power. The power is dominated by the first harmonic vibration and is closely correlated to the phase between the force and vibration velocity. Highlights: The energy harvesting device is an electromagnetic device attached to a cylinder elastically mounted in oscillatory flow. The lock-in power occurs when the natural frequency measured in water and the oscillatory flow frequency are the same. The lock-in power is affected by the electromagnetic damping ratio and there exists a best electromagnetic damping ratio. The best power is independent of the mass ratio and decreases with the increase of KC number. The best electromagnetic damping ratio decreases with the increase of mass ratio and increase with the increase of KC .